Maxillary Sinus Squamous Cell Carcinoma: A Clinical Study - Hohchi, Nobusuke; Wakasugi, Tetsuro; Takenaga, Fumiko; Takeuchi, Shoko; Ohkubo, Jun-ichi; Koizumi, Hiroki; Ohbuchi, Toyoaki; Suzuki, Hideaki (International Journal of Practical Otolaryngology, 2018)
We retrospectively analyzed the clinical characteristics and treatment outcomes of patients with maxillary sinus squamous cell carcinoma. The patients were 22 newly diagnosed cases of maxillary sinus squamous cell carcinoma who were treated at our institute between 2005 and 2016. There were 19 males and 3 females, ranging in age from 45 to 83 years (average age: 64.2 years). Our treatment protocol was as follows: All patients received chemoradiotherapy with weekly superselective intra-arterial administration of cisplatin (radiotherapy and concomitant intra-arterial cisplatin [RADPLAT]; 100–120 mg/body). Good responders at 30 to 40 Gy received additional radiotherapy (RADPLAT, ordinary chemoradiotherapy, or radiotherapy alone) until the total dose reached 72 Gy, whereas the other patients underwent radical surgery (partial maxillectomy, total maxillectomy, or extended total maxillectomy). The latter patients were given postoperative (chemo)radiotherapy up to a total dose of 72 Gy, when histopathological examination revealed insufficient resection or a positive surgical margin. The overall 5-year crude and disease-specific survival rates determined by the Kaplan–Meier method were 47.8 and 56.9%, respectively. The crude survival rate tended to be higher in T3 patients than in T4 patients (80.0 vs. 29.9%, p = 0.077). Seven patients died of the primary disease. The cause of death was distant metastasis in four patients, recurrence of the primary lesion in two patients, and cervical lymph node metastasis in one patient. These results suggest the importance of early detection and early treatment, and of the development of more effective treatment for advanced maxillary cancers, to further improve the survival rate.
Keywords: maxillary sinus squamous cell carcinoma; treatment outcome; survival rate; superselective intra-arterial chemoradiotherapy